Improving Students' Problem-Solving Skills and Self-Confidence through Ratiolib-Assisted Problem-Based Learning - Samosir, Binsar; Mujid, Abdul; Noviyanti, Mery (Indonesian Journal of Advanced Research, 2024)
The purpose of this study is to investigate and assess how the use of Problem-Based Learning (PBL) with RatioLib has improved the mathematical problem-solving abilities and self-confidence of seventh-grade students at SMP Maitreyawira Batam in the area of comparing two amounts. In this study, a mixed methods design is used. A quasi-experimental pretest-posttest control group approach is used in the quantitative phase. The two sets of research participants are the experimental group, which received PBL with RatioLib's assistance, and the control group, which received PBL without RatioLib. Tests were used to gauge mathematical problem-solving abilities, while questionnaires were used to gauge self-confidence. Several students participated in in-depth interviews throughout the qualitative phase to learn more about their learning experiences, opinions about RatioLib, and the elements affecting the development of their problem-solving abilities and self-assurance. The findings of the study should give a thorough picture of how PBL, with RatioLib's help, has been used to boost students' confidence and mathematical problem-solving abilities while also contributing to the creation of more efficient math instruction.